2019
DOI: 10.4314/jasem.v23i10.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Typha Grass on Biodiversity Loss of Hadejia-Nguru Wetland Located between Jigawa and Yobe States of Nigeria: A Review

Abstract: Wetland - an interface between terrestrial and aquatic ecosystems are the most precious life-sustaining water resources which play crucial roles as an ecosystem service provider. This paper reviewed the impact of Typha grass on biodiversity loss of Hadejia-Nguru wetland which is located between Jigawa and Yobe State of Nigeria. Impacts exerted by Typha grass on Hadejia-Nguru wetland includes that on biodiversity; impact on birdlife; creation of microhabitats that reduces habitat for wintering of migratory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The respondents reported that the weeds have reduced the water flow and caused blockage of channels. This view of the FGD discussants has been confirmed by several studies (Abubakar et al, 2016;Ndour et al, 2019;Zungum et al, 2019). The weeds have been affecting fishing activities because they affect water flows and fishing using nets and canoes.…”
Section: Impact Of Weeds On Fishingmentioning
confidence: 63%
See 1 more Smart Citation
“…The respondents reported that the weeds have reduced the water flow and caused blockage of channels. This view of the FGD discussants has been confirmed by several studies (Abubakar et al, 2016;Ndour et al, 2019;Zungum et al, 2019). The weeds have been affecting fishing activities because they affect water flows and fishing using nets and canoes.…”
Section: Impact Of Weeds On Fishingmentioning
confidence: 63%
“…On the other hand, focused on how typha grass is militating against agricultural productivity along Hadejia River. Similar studies in the area are those of Zungum et al (2019) and Salako et al (2016). However, the latter studied the impact of typha grass on biodiversity loss in the wetlands, while the former carried out a research on how typha contributes to wetland water loss and health risk in the wetlands.…”
Section: Introductionmentioning
confidence: 88%
“…There is a sustained rise in incidence of cancer and toxicity related to chemicals exerting enormous burden to public health and biodiversity (Zungum et al, 2019;Yaya et al, 2019;Sarki and Roni, 2019). Therefore, this review is aimed at further elaboration about the 16 United States Environmental Protection Agency (USEPA) characterized PAHs and their threat to public health and biodiversity.…”
Section: Introductionmentioning
confidence: 99%